1 COVID-19 in children treated with immunosuppressive medication for kidney diseases. (30th November 2020) - Marlais, Matko; Wlodkowski, Tanja; Schaefer, Franz; Tullus, Kjell
Abstract : Background: The impact of immunosuppressive therapy on children with COVID-19 is unclear. The aim of this study was to describe the clinical course of COVID-19 in children with kidney disease taking immunosuppressive medication and to assess the severity of their disease course. Methods: Prospective registry study hosted by the European Rare Kidney Disease Reference Network and supported by the European, Asian, and International paediatric nephrology societies. Anonymised data were submitted online for any child (age <20 years) with COVID-19 taking immunosuppressive medication for a kidney condition. The study was open for 16 weeks from 15/03/2020 – 05/07/2020. Primary outcome was Severity of COVID-19, graded 1–5. Secondary outcomes included impact of the underlying kidney condition and immunosuppressive medication on disease severity. Results: 113 children were reported in this study from 30 different countries. The median age was 13 years (49% male). The main underlying reasons for immunosuppressive therapy were; kidney transplant (47%), nephrotic syndrome (27%), SLE (10%), other glomerular disease or vasculitis (11%). Main immunosuppressive medications used include; glucocorticoids (76%), MMF (54%), tacrolimus/cyclosporine A (58%), Rituximab/Ofatumumab (11%). 78% required no respiratory support during their COVID-19 illness, 5% required BiPAP or ventilation. Four children died; all deaths reported were from low income countries and with associated co-morbidities. The mean severity of infection grade (1–5) was 2.4 in those where immunosuppression was reduced and 1.7 in those where it was not ( p =0.001). There was no significant difference in the severity of COVID-19, based on gender, dialysis status, underlying kidney condition, and type or number of immunosuppressive medications. Conclusions: This global study shows most children with a kidney disease needing treatment with immunosuppressive medication have mild disease with SARS-CoV-2 infection. We therefore suggest that children on immunosuppressive therapy should not be more strictly isolated than children who are not on immunosuppressive therapy.